Paroki, Wadah Perjumpaan Antarbudaya - Adicahyo, Agustinus Lintang; Pramudita, Nicolas Gerardus Dimas (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2020)
In this article, the writers try to ponder more deeply the meaning of unity in a parish congregation, since it has more and more become a place of intercultural encounter. In this way, the writers are also eager to offer some ideas for parish priests, the parish council, and the Christian congregations themselves, particularly in coping with interculturality, where the people of God from diverse backgrounds encounter. What then has to be taken into consideration in building up a so-called prosperous parish community? The writers underline the importance of intercultural competence for members of the community to realize the two main characters of the Church, namely the unity and the catholicity.